2013
DOI: 10.3109/15376516.2013.843106
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress enzyme status and frequency of micronuclei in heroin addicts in Turkey

Abstract: Heroin is among the most widely used and dangerous addictive opiate. The World Health Organization (WHO) estimated that more than 15 million people are under the influence of opiate addiction. The aim of this study was to investigate copper zinc-superoxide dismutase (Cu,Zn-SOD), catalase (CAT) and selenium-dependent glutathione peroxidase (Se-GPx) antioxidant enzyme activities, malondialdehyde (MDA) levels and the frequency of micronuclei (MN) in addicts using heroin, the most commonly abused opiate in Turkey.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…According to the world health organization (WHO), more than 15 million people are addicted to opiate (1). Opium (known as Taryak in Farsi) contains more than 40 types of alkaloids, such as morphine, codeine and thebaine, and over 70 other components including sugars and organic acids.…”
Section: Contextmentioning
confidence: 99%
“…According to the world health organization (WHO), more than 15 million people are addicted to opiate (1). Opium (known as Taryak in Farsi) contains more than 40 types of alkaloids, such as morphine, codeine and thebaine, and over 70 other components including sugars and organic acids.…”
Section: Contextmentioning
confidence: 99%
“…30,31 Furthermore, drug abusers are at oxidative stress. 32,33 Interestingly, the mRNA expression levels of several anti-oxidant genes significantly decreased in SH-SY5Y cells treated with morphine. 34 It has been reported that oxidative stress plays an important role in drug dependency.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that heroin and opium dependent persons are under oxidative stress conditions (Ghazavi et al, 2013;Soykut et al, 2013). We know that oxidative stress may occur due to increase in the generation of free radicals or in reduction in the level of antioxidant enzymes.…”
Section: To the Editorsmentioning
confidence: 98%
“…Opiates may cause oxidative stress in drug dependent persons (Ghazavi et al, 2013;Soykut et al, 2013). Glutathione S-transferases (GSTs) play an important role in cellular detoxification of xenobiotics.…”
Section: To the Editorsmentioning
confidence: 99%